Biosurfactant Activity of Bacillus sp. Strain LP04 Isolate and Its Antifungal Potency against Ganoderma boninense and Fusarium sp. - Maherani, Vincentia Fenice Angger; Mubarik, Nisa Rachmania; Priyanto, Jepri Agung; Putra, Ivan Permana (HAYATI Journal of Biosciences, 2024)
Biosurfactants are a class of amphipathic molecules that various microorganisms can produce. Biosurfactants are used as biopesticides and biocontrol agents because they have antimicrobial activity, especially as antifungal agents in several species of fungal pathogens such as Ganoderma boninense and Fusarium sp. that attack crops. This study aims to detect the biosurfactant activity of Bacillus sp. and its potential as an antifungal agent against the fungi Ganoderma boninense and Fusarium sp. Biosurfactants were produced in mineral salt medium (MSM) by harvesting cell-free supernatants. Screening of biosurfactant-producing isolates was carried out using an oil-spreading assay, a hemolysis assay, and an emulsification index. The antifungal activity of the isolates was then tested using the agar diffusion method. The LP04 isolate was closely related to Bacillus thuringiensis with a 99% similarity level. It has the potential to have biosurfactant activity, which is characterized by a positive result on the oil spreading assay test and has an emulsification index of 48.33±2.87%. The cell-free supernatants of the bacterial isolate were able to inhibit the growth of Ganoderma boninense and Fusarium sp. with growth inhibition rates of 51.11% and 56.92%, respectively.